2013
DOI: 10.1002/jctb.4007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the pre‐treatment alternatives on the treatment of oil‐gas field produced water by nanofiltration and reverse osmosis membranes

Abstract: BACKGROUND: Produced water is generated in huge volumes from oil and gas production facilities. Different alternatives including physical, chemical, and biological methods can be applied for the treatment of produced waters. In this study, different pre-treatment alternatives used before a final nanofiltration and reverse osmosis membrane system were evaluated. A membrane bioreactor and pressurized microfiltration and ultrafiltration systems were used in the pre-treatment stage.RESULTS: According to the result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 21 publications
2
23
0
2
Order By: Relevance
“…For example, the limit of BOD 5 concentration in treated effluent discharged to surface water is regulated in Colorado at 45 mg/L (Colorado Water Quality Control Commission, 2012). Furthermore, DOM may reduce the efficiency of RO desalination, through biofouling and decreasing of permeate flux (Lester et al, 2014;Ozgun et al, 2013). Removal of organic matter from wastewater is commonly carried out by biological processes, activated carbon adsorption or advanced oxidation processes (AOPs).…”
Section: Flowback Reuse Outside the Gas Industrymentioning
confidence: 99%
“…For example, the limit of BOD 5 concentration in treated effluent discharged to surface water is regulated in Colorado at 45 mg/L (Colorado Water Quality Control Commission, 2012). Furthermore, DOM may reduce the efficiency of RO desalination, through biofouling and decreasing of permeate flux (Lester et al, 2014;Ozgun et al, 2013). Removal of organic matter from wastewater is commonly carried out by biological processes, activated carbon adsorption or advanced oxidation processes (AOPs).…”
Section: Flowback Reuse Outside the Gas Industrymentioning
confidence: 99%
“…They found 12 E. Drioli et al / Desalination and Water Treatment experimentally that primary + oil/water separator + DAF system + 1 μm ceramic or metallic cartridge filter + 0.2 μm ceramic or metallic MF gave the best pretreatment option in terms of permeate flux and water quality before RO membranes. Ozgun et al [71] investigated the effect of different pretreatment options including MBR and pressurized MF and UF on the treatment of produced water using NF and RO. The authors observed that the maximum flux is obtained with MF/UF pretreatment combined with NF, while MBR combined with RO gives the best quality of the permeate in terms of conductivity and COD.…”
Section: Multitechnology Processesmentioning
confidence: 99%
“…Major uses of this technology are water filtration (including desalination) and purification (including groundwater and wastewater) as well as industries such as food and beverages and biotechnology (Kurt, Koseoglu, Dizge, Chellam, & Koyuncu, 2012;Ozgun et al, 2012). Continuing advances in regulatory constraints and aesthetic criteria for consumer water quality have driven the water community to seek new technologies.…”
Section: Membrane Filtration Technology For Water Treatmentmentioning
confidence: 99%